ANALISA PENGARUH PERUBAHAN BEBAN TERHADAP FREKUENSI GENERATOR SATU PHASA - Simamora, Antonius; Sinaga, Joslen; Mutiara, Piala; Mariaty, Linda; Sitohang, Rasmi (Universitas Medan Area, 2023)
Generators are equipment that converts mechanical energy into electrical energy by utilizing the electromagnetic principle in converting its energy, where the mechanical energy can be obtained from prime movers such as diesel engines (PLTD), hydropower (PLTA), gas power (PLTG). , geothermal (PLTPB). Frequency can also be used as a measure of the instantaneous balance between the real power (MW) consumed by consumers (load) and the real power supply from power plants. Setting the excitation current given to the generator so that the generator produces a voltage of 220 volts. electrical systems, generators and components connected with a complete interconnection system to connect several generators and consumers. To supply power from generators to consumers, system reliability is needed, where one of the requirements for an electric power system is said to be reliable if it fulfills the requirements for generating system reliability such as voltage and frequency values, especially in terms of frequency must be within the specified limits (1 % of the standard frequency), where the standard frequency in Indonesia is 50 Hz.